An optimized isolation protocol yields high‐quality RNA from cassava tissues (Manihot esculenta Crantz) - Behnam, Babak; Bohórquez Cháux, Adriana; Castañeda Méndez, Oscar F.; Tsuji, Hiroyuki; Ishitani, Manabu; Becerra López Lavelle, Luis Augusto (Wiley, 2018)
We developed and modified a precise, rapid, and reproducible protocol isolating high‐quality RNA from tissues of multiple varieties of cassava plants (Manihot esculenta Crantz). The resulting method is suitable for use in mini, midi, and maxi preparations and rapidly achieves high total RNA yields (170–600 μg/g) using low‐cost chemicals and consumables and with minimal contamination from polysaccharides, polyphenols, proteins, and other secondary metabolites. In particular, A260:A280 ratios were >2.0 for RNA from various tissues, and all of the present RNA samples yielded ribosomal integrity number values of greater than six. The resulting high purity and quality of isolated RNAs will facilitate downstream applications (quantitative reverse transcriptase‐polymerase chain reaction or RNA sequencing) in cassava molecular breeding.